(untitled) (Global Journal of Human-Social Science, 2018)
This study examined the suitability of Theory of Optimum Currency as a basis for feasibility of proposed monetary union in East African Community EAC countries Uganda Burundi Kenya Rwanda and Tanzania The study sought to determine symmetry of monetary shocks inflation rates fiscal deficit public debt real Gross Domestic Product GDP and degree of openness Exploratory was used employing panel data covering 2000Q1-2016Q4 Generalized Method of Moments approach was utilized Results showed convergence in the real exchange rate was statistically significant and negative implying formation of a monetary union reduced combined GDP Policy makers in EAC countries could concentrate in adapting unfulfilled macroeconomic convergence criteria and strengthening cooperation in monetary policy co-ordinations